2020
DOI: 10.3138/canlivj.2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of prolonged disengagement from clinic among people with HCV receiving care in a low-threshold, multidisciplinary clinic

Abstract: BACKGROUND: Disengagement from care can affect treatment outcomes of patients with hepatitis C virus (HCV). We assessed the extent and determinants of disengagement among HCV patients receiving care at the Ottawa Hospital Viral Hepatitis Program (TOHVHP). METHODS: We linked clinical data of adult patients, categorized as ever or never disengaged from clinic (no TOHVHP encounters over 18 months), receiving care between April 1, 2002, and October 1, 2015, to provincial health administrative databases and calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, prior studies have indicated that follow-up for chronic illnesses can be challenging [ 8 , 9 ]. Disengagement from care is sometimes frequent due to a number of factors that impact healthcare services in sub-Saharan Africa (SSA), including insufficient healthcare infrastructure and out-of-pocket expenses [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, prior studies have indicated that follow-up for chronic illnesses can be challenging [ 8 , 9 ]. Disengagement from care is sometimes frequent due to a number of factors that impact healthcare services in sub-Saharan Africa (SSA), including insufficient healthcare infrastructure and out-of-pocket expenses [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%